Audience Labour pada Media Sosial (Studi pada Fitur Instagram) - Widyanty, Resty (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Communication theory has a broad and dynamic audience concept when discussing about public behavior and its relations with the media. Now profileration of technology such as internet supports the change in behavioral characteristics of the audience, it becomes more active or can be said it becomes hyperactive. Social media such as Instagram also support that notion in the nature of the audience by providing space and features that giving an easier  process of content production by audiences. These features are mainly perceived to support the practice of mobilizing audiences by making the user as a labour. When discussing the mobilization of audiences, Eran Fisher provides three ways social media mobilize audiences to gain surplus value and make audiences as high resources workforce. That concept happens through the process of consumption, production, and marketing by audience. This paper discusses how Instagram, through these three ways, mobilize audiences and make them as audience labor.